Polya partial gastrectomy for megaduodenum: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Megaduodenum is an extremely rare condition in children presenting with features of duodenal obstruction. It may be associated with bands and adhesions. However, when the obstruction is chronic and functional, mere excision of the band and adhesionolysis is not curative. Some form of bypass procedure is required for its successful treatment. Here we are describing polya partial gastrectomy in a 13-year-old girl suffering from megadoudenum for its successful treatment.